The vein of Galen aneurysmal malformation associated with Turner syndrome mosaicism -a case report - Livrinova, Vesna; Irena Todorovska; Shukarova Angelovska, Elena; Ristovska, Sanja; Dimitrovska, Renata; Simeonova krstevska, Slagjana; Stomnaroska, Orhidea (Creative Commons Attribution License, MSD Publications, 2024)
Prenatal diagnosis of the vein of Galen aneurysmal malformation. Congenital malformation develops during weeks 6-11 of fetal development as a persistent embryonic prosencephalic vein of Markowski. The incidence of this malformation is estimated to be high. The true incidence is unknown but estimated to be 1 in 10,000 to 1 in 25,000 births. malformation accounts for 30% of pediatric congenital vascular malformations and about 1% of all pediatric congenital anomalies. Infants often die of high-output congestive heart failure [1,2]. The presenting case report’s main aim is to illustrate the disease with ultrasound performed during pregnancy and Magnetic resonance characteristics, postnatal evaluation, parenteral counseling, and their decision for further treatment in the neighboring country [3]. It should be stressed that the fetus has mosaicism of Turner Syndrome, two lines, normal and unusual abnormal form. The pregnancy was 34 gestational weeks with intrauterine growth restriction. The limitation in the precision of prenatal diagnosis at primary care obstetricians and the use of additional diagnostics tools for improving the diagnosis can lead to unwanted events of pregnancy, like intrauterine fetal demise. This does not happen in this case
Turner syndrome (TS) is one of the most common sex chromosome abnormalities and results from total or partial monosomy of the X chromosome. It occurs in 1 in 2000 newborn girls and is also believed to be present in a larger proportion of conceptuses. Various anatomic anomalies have been associated with TS and the consequences of late recognition of these anomalies can be devastating.
Keywords: vein of Galen; malformation; Turner syndrome; mosaicism